Effects of cutting speeds, moisture contents and sweet potato varieties on tractor fuel consumption - Kakahy, Amer Najat Najmaldeen; Ahmad, Desa; Hamid, Md. Akhir; Sulaiman, Shamsuddin; Aris, Ishak (Faculty of Engineering, Universiti Putra Malaysia, 2016)
A study was conducted to test the effects of three mower cutting speeds (2300, 2500 and 2700 rpm), three varieties of sweet potato (VitAto, Orange and Stone) at three different moisture contents of the plant (22.4, 30.39 and 41.06 %), wet base (wb %) on tractor fuel consumption (ml/m). The results showed that all the treatments were significant at p ‹ 0.01 significance level for fuel consumption (ml/m). The best fuel consumption of 1.49 ml/m was achieved when using the Stone variety of sweet potato at 22.4 % moisture content and 2300 rpm mower speed. Data were analyzed statistically using ANOVA and the least significant difference LSD calculated at 1 % to estimate the differences between the averages.